Self-referred walk-in patients in the emergency department - who and why? Consultation determinants in a multicenter study of respiratory patients in Berlin, Germany - Felix Holzinger; Sarah Oslislo; Martin Möckel; Liane Schenk; Mareen Pigorsch; Christoph Heintze (BMC, 2020)
Abstract Background Emergency department (ED) consultations are on the rise, and frequently consultations by non-urgent patients have been held accountable. Self-referred walk-in (SRW) consulters supposedly represent a predominantly less urgent patient population. The EMACROSS study aimed to explore consultation determinants and motives in SRW patients with respiratory symptoms. Methods Multicenter survey of adult ED patients with respiratory complaints in eight emergency departments in central Berlin, Germany. Secondary hospital records data including diagnoses was additionally assessed. Characteristics of SRW and non-SRW patients were compared. Determinants of SRW consultation were evaluated by binary logistic regression. Consultation motives were analyzed descriptively. As a supplemental approach, network analysis (lasso-regularized mixed graphical model) was performed to explore connections between consultation determinants, consultation features and motives. Results Between June 2017 and November 2018, n = 472 participants were included, the median age was 55 years (range 18-96), 53.2% of patients were male and n = 185 cases (39.2%) were SRW consulters. The SRW group showed lower proportions of potentially severe (pneumonia and respiratory failure, p < 0.001, χ2 test) and chronic pulmonary conditions. Determinants of SRW consultation identified by logistic regression were younger age (p < 0.001), tertiary education (p = 0.032), being a first-generation migrant (p = 0.002) or tourist (p = 0.008), having no regular primary care provider (p = 0.036) and no chronic pulmonary illness (p = 0.017). The area under the curve (AUC) for the model was 0.79. Personal distress and access problems in ambulatory care were stated most frequently as consultation motives in the SRW group; network analysis showed the scarcity of associations between demographic and medical SRW determinants and motives triggering the actual decision to consult. Conclusions As to "who" consults, this study identified demographic and medical predictors of SRW utilization. The said markers seem only remotely connected to "why" people decide for SRW visits. To alleviate ED crowding by addressing frequent SRW consultation motives, interventions focused on the ability for symptom self-assessment and at better-accessible alternative care seem sensible. Trial registration German Clinical Trials Register ( DRKS00011930 ); date: 2017/04/25.